Perbandingan Kinerja Redis, Mosquitto, dan MongoDB sebagai Message Broker pada IoT Middleware - Fitri Febriyani; Eko Sakti Pramukantoro; Fariz Andri Bachtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
IoT middleware has a service unit that implements Redis message broker to accept various types of data. In addition to receiving data, message brokers need to be scalable to handle a lot of data and to continue to operate despite failures. This study compares the performance of Redis, Mosquitto, and MongoDB as alternating message brokers on IoT middleware. MongoDB was chosen because of its scalability and Mosquitto was chosen because of its stable performance. The results of performance testing, the best CPU usage when reading data is Mosquitto with a range of 8%-62%. CPU usage when writing data, memory usage, and runtime, Redis has the best results with values ​​ranging from 13%-41%, 53MB-64MB and 54MB-59MB. Then the write and read data runtime are 2,37 seconds and 0,05 seconds. On disk i/o, MongoDB has the best performance when writing and reading data of 111 megabits and 689 megabits. In terms of scalability, the best concurrent publish is Mosquitto for 18 messages per second through CoAP and 15 messages per second through MQTT. It can be concluded that Redis has a good performance on CPU usage when writing data, memory usage, runtime, and speed of handling incoming data. In terms of disk i/o and speed of reading data, MongoDB has the best performance. Whereas Mosquitto has the speed of writing data and handling data that comes out.